Impact of Leadership Style on Employee Performance And Job Satisfaction Among Jordanian Physiotherapists - Hashem Nader Aljaddouih; Mohammed Yousef Alkhraishi (ACHSM, 2024)
Leadership philosophies are essential organizational practices, especially when it comes to promoting and enhancing worker collaboration and job satisfaction. This study aims to ascertain and explore the relationship between job satisfaction and job performance among Jordanian physiotherapists and transformational leadership. Additionally, looks at whether job satisfaction and organizational citizenship behaviours operate as a mediator in the link between transformational leadership and worker performance. This study's design involves a quantitative correlation analysis conducted on a conveniently chosen sample of Jordanian physiotherapists from different healthcare facilities to examine the relationship between their performance level and leadership practices, specifically transformational leadership style, as well as any potential mediating role that organizational citizenship behaviours and job satisfaction may have on that relationship. Additionally, an online questionnaire for 123 physiotherapists in a different facility is used to study the proposed relation connecting transformational leadership style and therapist satisfaction level. Data were acquired about performance, job satisfaction, and organizational citizenship behaviours of therapists as well as their opinions of the leadership styles exhibited by the facility leaders. Organizational citizenship behaviours (OCB) and job satisfaction (JS) fully mediated the relationship between transformational leadership and physiotherapy performance; as a result, the impact of transformational leadership style (TLS) on performance was indirect since the direct influence wasn't statistically significant. Additionally, TLS has a positive and substantial impact on job satisfaction and organizational citizenship behaviours by regression analysis; likewise, OCB and JS have a positive significant effect on performance (p-value <.001). Transformational leadership and performance among Jordanian physiotherapists are not significant directly but are significant indirectly by the mediator (OCB and JS). Because it impacts worker job satisfaction, the standard of healthcare services provided, and the patient experience in this organization, it encourages the development of transformational leadership abilities in healthcare facilities and ongoing training for leaders in this area.